HUBUNGAN ANTARA PENGETAHUAN DAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI KABUPATEN BADUNG - Kadek Agus Dwija Putra (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2019)
Background: The prevalence of anemia in adolescent girls in Indonesia according to WHO reaches 30%, and in the 2013 Riskesdas report recorded 18.4% of adolescents have anemia with the highest percentage in the female sex of 23.9%. Anemia in adolescents can cause delay in physical growth and behavior and emotional disorders. This study aims to determine the relationship between knowledge about anemia and nutritional status with the incidence of anemia in young women in Badung Regency. Method: This study uses analytic cross sectional design with a sample of 106 adolescent girls aged 15-18 years in high school, Badung Regency. Data collection was carried out directly on respondents in each school, for anemia data was collected by examining blood samples or hematology panels (hemograms) with an Hematology Autoanalyzer tool, data on knowledge of anemia was carried out by means of interviews using questionnaire guidelines, and nutritional status data was carried out by how to measure anthropometry (body weight and height) to get a IMT value. The analysis conducted is univariate analysis to determine the distribution and frequency of variables and bivariate analysis using the Kai-Kuadrat/Chi-Square test with the help of the SPSS program. Result: The prevalence of anemia in young women is 13.2%. Most had normal nutritional status of 77.4%, while others were categorized as abnormal / malnutrition (2.8% thin, 17.0% fat, 2.8% obese). For the level of knowledge obtained, the majority of 77.4% have a good level of knowledge in the category of anemia. Kai-Square / Chi-Square test results showed that, there was a significant relationship between knowledge about anemia and anemia in adolescent girls (95% CI: 1.93-20.77; p = 0.003). There was no significant relationship between nutritional status and anemia in adolescent girls (p = 0.301). Conclusion: Poor knowledge about anemia is associated with the incidence of anemia in young women, whereas nutritional status is not related to the incidence in young women. It is expected that related parties make a policy regarding anemia screening and education activities especially for young women. Keywords: Anemia; Knowledge; Nutritional status